A composite filler filled high-toughness corrosion-resistant copper-clad laminate and preparation method thereof

By using composite filler technology in copper clad plates, materials such as fluorinated graphene, modified cellulose-aluminum hydroxide composite and uucol are uniformly dispersed in epoxy resins, solving the problems of easy corrosion and fragile mechanical properties in high-corrosive environments, and achieving high toughness, corrosion-resistant copper clad plate preparation.

CN119099182BActive Publication Date: 2025-03-18JIANG SU YAO HONG ELECTRONICS CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411231572.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-04
Publication Date
2025-03-18
Estimated Expiration
2044-09-04

AI Technical Summary

Technical Problem

Traditional copper clad plates are prone to corrosion in highly corrosive environments and have weak mechanical properties. The prior art improves performance by adding fillers but the fillers are difficult to disperse, resulting in a decrease in toughness.

Method used

By adopting the composite filler preparation method, materials such as fluorinated graphene, modified cellulose-aluminum hydroxide composite and uucol are uniformly dispersed in the epoxy resin to form a high toughness and corrosion-resistant copper clad plate.

Benefits of technology

The corrosion resistance and mechanical properties of the copper clad plate are significantly improved, and the toughness reduction caused by poor dispersion of fillers is avoided.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005026301540000101
    Figure BDA0005026301540000101
Patent Text Reader

Abstract

The present invention relates to the technical field of copper-clad substrates, specifically to a composite filler-filled high-toughness corrosion-resistant copper-clad laminate and a preparation method thereof. The present invention uses aluminum hydroxide as a filler doped in an epoxy resin composition, which can not only improve the corrosion resistance of the copper-clad laminate, but also improve the mechanical properties of the copper-clad laminate. The present invention uses fluorinated graphene, which has good mechanical properties. Adding it to epoxy resin to modify the copper-clad laminate can also improve the corrosion resistance of the copper-clad laminate. The cellulose-aluminum hydroxide complex in the present invention synergistically modifies the epoxy resin with lacquer phenol, reduces the surface energy of the copper-clad laminate, and improves the corrosion resistance of the copper-clad laminate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of copper-clad substrates, in particular to a composite filler-filled high-toughness corrosion-resistant copper-clad laminate and a preparation method thereof. Background Art

[0002] With the development of 5G technology, the demand for circuit boards is increasing, and the requirements are getting higher and higher. Therefore, the substrates used to manufacture circuit boards are becoming more and more important. With the continuous development of electronic equipment, the performance requirements for circuit boards are also getting higher and higher. Especially in some special environments, such as highly corrosive environments or extremely high requirements for mechanical properties, traditional copper clad laminates are often difficult to meet the needs. Traditional copper clad laminates may have corrosion problems in highly corrosive environments, and may be brittle in terms of mechanical properties. In order to overcome these problems, some attempts in the prior art have been made to improve the performance of copper clad laminates by adding fillers, but the large addition of fillers will make it difficult to disperse the fillers, thereby causing the toughness of the copper clad laminates to decrease, affecting the performance of the copper clad laminates.

[0003] In order to improve the corrosion resistance and toughness of a circuit board, the present invention provides a composite filler filled high-toughness corrosion-resistant copper clad laminate and a preparation method thereof. Summary of the invention

[0004] The object of the present invention is to provide a composite filler filled high toughness corrosion resistant copper clad laminate and a preparation method thereof, so as to solve the problems raised in the above background technology.

[0005] In order to solve the above technical problems, the present invention provides the following technical solutions:

[0006] A method for preparing a composite filler-filled high-toughness corrosion-resistant copper-clad laminate comprises the following steps:

[0007] Step 1: Take urushiol and anhydrous ethanol, stir evenly, add fluorinated graphene, ultrasonically disperse, heat to 95-100° C., stir for 24-26 hours, add modified cellulose-aluminum hydroxide complex, continue stirring for 70-74 hours, filter, wash, and dry to obtain urushiol-modified composite filler;

[0008] Step 2: Take lacquer phenol modified composite filler and deionized water, stir evenly, add polyethylene glycol diglycidyl ether, stir at 80-85° C. until the deionized water is completely evaporated, add bisphenol A diglycidyl ether, stir for 2-3 hours, cool, add polyetheramine, stir evenly, evacuate, and obtain modified epoxy resin;

[0009] Step 3: Take the modified epoxy resin, epoxy resin, dicyandiamide, 2-methylimidazole, silicon dioxide, and an organic solvent, heat at 90-95° C., mix well, and cool to obtain an epoxy resin composition;

[0010] Step 4: Take the epoxy resin composition to impregnate glass cloth, dry it to obtain a prepreg; take 3-4 prepregs and overlap them, cover the upper and lower surfaces with electrolytic copper foil, and hot press them at 210-220°C to obtain a copper clad laminate.

[0011] More optimally, the preparation method of the fluorinated graphene is: take polyvinyl pyrrolidone and ethanol, stir evenly, add fluorinated graphene, ultrasonically disperse, then stir for 10-12 hours, centrifuge, take the supernatant, filter, wash, and dry to obtain fluorinated graphene.

[0012] More optimally, the preparation method of the modified cellulose-aluminum hydroxide complex is: take ethanol and deionized water, add glacial acetic acid dropwise, add a silane coupling agent, stir for 30-40 minutes, add the cellulose-aluminum hydroxide complex, heat to 65-70°C, stir for 7-9 hours, filter, wash, and dry to obtain the modified cellulose-aluminum hydroxide complex.

[0013] More optimally, the preparation method of the cellulose-aluminum hydroxide complex is: take cellulose and anhydrous ethanol, stir evenly, add OP-10 emulsifier dropwise, stir for 20-30 minutes, add aluminum chloride aqueous solution, stir for 15-20 minutes, heat to 55-65°C, slowly add sodium bicarbonate solution, stir for 2-2.5 hours, filter, wash, and dry to obtain a cellulose-aluminum hydroxide complex.

[0014] More optimally, the silane coupling agent is 3-glycidyloxypropyltrimethoxysilane.

[0015] More optimally, in step 1, the mass ratio of urushiol, fluorinated graphene, and modified cellulose-aluminum hydroxide composite is (6-7): (0.1-0.3): (2-3).

[0016] More optimally, the mass ratio of urushiol, fluorinated graphene, and modified cellulose-aluminum hydroxide composite is 6:(0.2-0.3):(2-2.5).

[0017] More optimally, the epoxy resin composition comprises the following ingredients: 270-290 parts of modified epoxy resin, 130-140 parts of epoxy resin, 55-60 parts of dicyandiamide, 0.2-0.4 parts of 2-methylimidazole, 10-15 parts of silicon dioxide, and 80-90 parts of organic solvent.

[0018] Compared with the prior art, the beneficial effects achieved by the present invention are:

[0019] (1) The present invention uses aluminum hydroxide as a filler doped into the epoxy resin composition, which can not only improve the corrosion resistance of the copper clad laminate, but also improve the mechanical properties of the copper clad laminate.

[0020] (2) The present invention uses fluorinated graphene, which has good mechanical properties. Adding fluorinated graphene to epoxy resin to modify the copper clad laminate can also improve the corrosion resistance of the copper clad laminate.

[0021] (3) Urushiol has a catechol group and a carbon long alkyl chain, is a polydopamine derivative, and also has a certain degree of adhesion. The long alkyl chain can also reduce the surface energy, further enhancing the corrosion resistance of the copper clad laminate. The present invention first uses 3-glycidyloxypropyltrimethoxysilane to modify the cellulose-aluminum hydroxide composite, and grafts epoxy groups on the cellulose-aluminum hydroxide composite. The epoxy groups can react with the hydroxyl groups in the urushiol, and the fluorinated graphene and the modified cellulose-aluminum hydroxide composite are compounded together, thereby improving the dispersibility of the fluorinated graphene and the modified cellulose-aluminum hydroxide composite.

[0022] Secondly, the aluminum hydroxide in the cellulose-aluminum hydroxide composite is at the micron level. The micron-level rough structure provided by the aluminum hydroxide and the low surface energy provided by the lacquer phenol synergistically modify the epoxy resin, thereby reducing the surface energy of the copper clad laminate and improving the corrosion resistance of the copper clad laminate. DETAILED DESCRIPTION

[0023] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0024] There is no special restriction on the purchase manufacturers of all raw materials involved in the present invention, and illustratively include: cellulose: microcrystalline cellulose, which can be purchased from Sigma-Aldrich (Shanghai) Trading Co., Ltd., item number: Y0002021; graphite fluoride: can be purchased from Shanghai Fubon Chemical Co., Ltd., fluorine-carbon ratio 0.8-1.1, average particle size 4-6 microns; urushiol: 15:1, model: B75650, can be purchased from Shanghai Yuanye; polyethylene glycol diglycidyl ether: can be purchased from Shanghai Aladdin Chemical Reagent Co., Ltd.; bisphenol A diglycidyl ether: E51, can be purchased from Hangzhou Wujingang Adhesive Co., Ltd.; polyether amine: D-230, can be purchased from Shanghai Aladdin Chemical Reagent Co., Ltd.; epoxy resin: CYD-128 type, can be purchased from China Petrochemical Group Baling Petrochemical Branch.

[0025] Embodiment 1: A method for preparing a composite filler-filled high-toughness corrosion-resistant copper-clad laminate, comprising the following steps:

[0026] Step 1: Preparation of cellulose-aluminum hydroxide complex:

[0027] Take 20g of cellulose and 120mL of anhydrous ethanol, stir evenly, add 0.2g of OP-10 emulsifier dropwise, stir for 25min, add 40g of 16.7wt% aluminum chloride aqueous solution, stir for 18min, heat to 60°C, slowly add 100mL of 8wt% sodium bicarbonate solution, stir for 2.3h, filter, wash and dry to obtain cellulose-aluminum hydroxide composite;

[0028] Step 2: Preparation of modified cellulose-aluminum hydroxide composite:

[0029] Take 80 mL of ethanol and 4 mL of deionized water, add glacial acetic acid dropwise, adjust the pH value of the solution to 4, add 2 mL of 3-glycidyloxypropyltrimethoxysilane, stir for 35 min, add 1.5 g of cellulose-aluminum hydroxide complex, heat to 67 ° C, stir for 8 h, filter, wash and dry to obtain a modified cellulose-aluminum hydroxide complex;

[0030] Step 3: Preparation of fluorinated graphene:

[0031] Take 1 g of polyvinyl pyrrolidone and 100 mL of ethanol, stir evenly, add 0.2 g of fluorinated graphene, disperse by ultrasonication, then stir for 11 h, centrifuge, take the supernatant, filter, wash, and dry to obtain fluorinated graphene;

[0032] Step 4: Preparation of urushiol-modified composite filler:

[0033] Take 6 g of urushiol and 100 mL of anhydrous ethanol, stir evenly, add 0.2 g of fluorinated graphene, disperse by ultrasonication, heat to 97 ° C, stir for 25 h, add 2 g of modified cellulose-aluminum hydroxide composite, continue stirring for 72 h, filter, wash, and dry to obtain urushiol-modified composite filler;

[0034] Step 5: Preparation of modified epoxy resin:

[0035] Take 7g of lacquer phenol modified composite filler and 50mL of deionized water, stir evenly, add 33g of polyethylene glycol diglycidyl ether, stir at 83°C until the deionized water is completely evaporated, add 78g of bisphenol A diglycidyl ether, stir for 2.5h, cool, add 20.5g of polyetheramine, stir evenly, evacuate, and obtain modified epoxy resin.

[0036] Step 6: Preparation of copper clad laminate:

[0037] Preparation of epoxy resin composition:

[0038] Take modified epoxy resin, epoxy resin, dicyandiamide, 2-methylimidazole, silicon dioxide, and organic solvent dimethylformamide, heat at 93° C., mix well, and cool to obtain an epoxy resin composition;

[0039] The epoxy resin composition comprises the following ingredients: 280 parts of modified epoxy resin, 135 parts of epoxy resin, 57 parts of dicyandiamide, 0.2 parts of 2-methylimidazole, 12 parts of silicon dioxide, and 85 parts of organic solvent dimethylformamide;

[0040] Take the epoxy resin composition to impregnate 7628 glass cloth, dry it at 125℃ to obtain a prepreg; take 3 prepregs and overlap them, cover the upper and lower surfaces with 35μm thick electrolytic copper foil, and heat it at 215℃ with 25Kg / cm 2 The copper clad laminate was obtained by hot pressing for 190 min.

[0041] Embodiment 2: A method for preparing a composite filler-filled high-toughness corrosion-resistant copper-clad laminate, comprising the following steps:

[0042] Step 1: Preparation of cellulose-aluminum hydroxide complex:

[0043] Take 20g of cellulose and 120mL of anhydrous ethanol, stir evenly, add 0.2g of OP-10 emulsifier dropwise, stir for 20min, add 40g of 16.7wt% aluminum chloride aqueous solution, stir for 15min, heat to 55°C, slowly add 100mL of 8wt% sodium bicarbonate solution, stir for 2h, filter, wash and dry to obtain cellulose-aluminum hydroxide composite;

[0044] Step 2: Preparation of modified cellulose-aluminum hydroxide composite:

[0045] Take 80 mL of ethanol and 4 mL of deionized water, add glacial acetic acid dropwise, adjust the pH value of the solution to 4, add 2 mL of 3-glycidyloxypropyltrimethoxysilane, stir for 30 min, add 1.5 g of cellulose-aluminum hydroxide complex, heat to 65 ° C, stir for 7 h, filter, wash and dry to obtain a modified cellulose-aluminum hydroxide complex;

[0046] Step 3: Preparation of fluorinated graphene:

[0047] Take 1 g of polyvinyl pyrrolidone and 100 mL of ethanol, stir evenly, add 0.2 g of fluorinated graphene, disperse by ultrasonication, then stir for 10 h, centrifuge, take the supernatant, filter, wash, and dry to obtain fluorinated graphene;

[0048] Step 4: Preparation of urushiol-modified composite filler:

[0049] Take 6 g of urushiol and 100 mL of anhydrous ethanol, stir evenly, add 0.1 g of fluorinated graphene, disperse by ultrasonication, heat to 95°C, stir for 24 h, add 2 g of modified cellulose-aluminum hydroxide composite, continue stirring for 70 h, filter, wash, and dry to obtain urushiol-modified composite filler;

[0050] Step 5: Preparation of modified epoxy resin:

[0051] Take 7g of lacquer phenol modified composite filler and 50mL of deionized water, stir evenly, add 33g of polyethylene glycol diglycidyl ether, stir at 80°C until the deionized water is completely evaporated, add 78g of bisphenol A diglycidyl ether, stir for 2h, cool, add 20.5g of polyetheramine, stir evenly, evacuate, and obtain modified epoxy resin.

[0052] Step 6: Preparation of copper clad laminate:

[0053] Preparation of epoxy resin composition:

[0054] Take modified epoxy resin, epoxy resin, dicyandiamide, 2-methylimidazole, silicon dioxide, and organic solvent dimethylformamide, heat at 90° C., mix well, and cool to obtain an epoxy resin composition;

[0055] The epoxy resin composition comprises the following ingredients: 270 parts of modified epoxy resin, 130 parts of epoxy resin, 55 parts of dicyandiamide, 0.2 parts of 2-methylimidazole, 10 parts of silicon dioxide, and 80 parts of organic solvent dimethylformamide;

[0056] Take the epoxy resin composition to impregnate 7628 glass cloth, dry it at 120℃ to obtain a prepreg; take 3 prepregs and overlap them, cover the upper and lower surfaces with 35μm thick electrolytic copper foil, and heat it at 210℃ with 25Kg / cm 2 The copper clad laminate was obtained by hot pressing for 180 min.

[0057] Embodiment 3: A method for preparing a composite filler-filled high-toughness corrosion-resistant copper-clad laminate, comprising the following steps:

[0058] Step 1: Preparation of cellulose-aluminum hydroxide complex:

[0059] Take 20g of cellulose and 120mL of anhydrous ethanol, stir evenly, add 0.2g of OP-10 emulsifier dropwise, stir for 30min, add 40g of 16.7wt% aluminum chloride aqueous solution, stir for 20min, heat to 65°C, slowly add 100mL of 8wt% sodium bicarbonate solution, stir for 2.5h, filter, wash and dry to obtain cellulose-aluminum hydroxide composite;

[0060] Step 2: Preparation of modified cellulose-aluminum hydroxide composite:

[0061] Take 80 mL of ethanol and 4 mL of deionized water, add glacial acetic acid dropwise, adjust the pH value of the solution to 4, add 2 mL of 3-glycidyloxypropyltrimethoxysilane, stir for 40 min, add 1.5 g of cellulose-aluminum hydroxide complex, heat to 70 ° C, stir for 9 h, filter, wash and dry to obtain a modified cellulose-aluminum hydroxide complex;

[0062] Step 3: Preparation of fluorinated graphene:

[0063] Take 1 g of polyvinyl pyrrolidone and 100 mL of ethanol, stir evenly, add 0.2 g of fluorinated graphene, disperse by ultrasonication, then stir for 12 h, centrifuge, take the supernatant, filter, wash, and dry to obtain fluorinated graphene;

[0064] Step 4: Preparation of urushiol-modified composite filler:

[0065] Take 6 g of urushiol and 100 mL of anhydrous ethanol, stir evenly, add 0.3 g of fluorinated graphene, disperse by ultrasonication, heat to 100 ° C, stir for 26 h, add 2.5 g of modified cellulose-aluminum hydroxide composite, continue stirring for 74 h, filter, wash, and dry to obtain urushiol-modified composite filler;

[0066] Step 5: Preparation of modified epoxy resin:

[0067] Take 7g of lacquer phenol modified composite filler and 50mL of deionized water, stir evenly, add 33g of polyethylene glycol diglycidyl ether, stir at 85°C until the deionized water is completely evaporated, add 78g of bisphenol A diglycidyl ether, stir for 3h, cool, add 20.5g of polyetheramine, stir evenly, evacuate, and obtain modified epoxy resin.

[0068] Step 6: Preparation of copper clad laminate:

[0069] Preparation of epoxy resin composition:

[0070] Take the modified epoxy resin, epoxy resin, dicyandiamide, 2-methylimidazole, silicon dioxide, and organic solvent dimethylformamide, heat at 95° C., mix well, and cool to obtain an epoxy resin composition;

[0071] The epoxy resin composition comprises the following components: 290 parts of modified epoxy resin, 140 parts of epoxy resin, 60 parts of dicyandiamide, 0.4 parts of 2-methylimidazole, 15 parts of silicon dioxide, and 90 parts of organic solvent dimethylformamide;

[0072] Take the epoxy resin composition to impregnate 7628 glass cloth, dry it at 130℃ to obtain a prepreg; take 3 prepregs and overlap them, cover the upper and lower surfaces with 35μm thick electrolytic copper foil, and heat it at 220℃ with 25Kg / cm 2The copper clad laminate was obtained by hot pressing at a pressure of 200 min.

[0073] Comparative Example 1: No urushiol was added, and the rest was the same as Example 1:

[0074] Step 1: Preparation of cellulose-aluminum hydroxide complex:

[0075] Take 20g of cellulose and 120mL of anhydrous ethanol, stir evenly, add 0.2g of OP-10 emulsifier dropwise, stir for 25min, add 40g of 16.7wt% aluminum chloride aqueous solution, stir for 18min, heat to 60°C, slowly add 100mL of 8wt% sodium bicarbonate solution, stir for 2.3h, filter, wash and dry to obtain cellulose-aluminum hydroxide composite;

[0076] Step 2: Preparation of modified cellulose-aluminum hydroxide composite:

[0077] Take 80 mL of ethanol and 4 mL of deionized water, add glacial acetic acid dropwise, adjust the pH value of the solution to 4, add 2 mL of 3-glycidyloxypropyltrimethoxysilane, stir for 35 min, add 1.5 g of cellulose-aluminum hydroxide complex, heat to 67 ° C, stir for 8 h, filter, wash and dry to obtain a modified cellulose-aluminum hydroxide complex;

[0078] Step 3: Preparation of fluorinated graphene:

[0079] Take 1 g of polyvinyl pyrrolidone and 100 mL of ethanol, stir evenly, add 0.2 g of fluorinated graphene, disperse by ultrasonication, then stir for 11 h, centrifuge, take the supernatant, filter, wash, and dry to obtain fluorinated graphene;

[0080] Step 4: Preparation of composite fillers:

[0081] Take 100 mL of anhydrous ethanol, add 0.2 g of fluorinated graphene, disperse by ultrasonication, heat to 97°C, stir for 25 h, add 2 g of modified cellulose-aluminum hydroxide composite, continue stirring for 72 h, filter, wash, and dry to obtain a composite filler;

[0082] Step 5: Preparation of modified epoxy resin:

[0083] Take 7g of composite filler and 50mL of deionized water, stir evenly, add 33g of polyethylene glycol diglycidyl ether, stir at 83°C until the deionized water is completely evaporated, add 78g of bisphenol A diglycidyl ether, stir for 2.5h, cool, add 20.5g of polyetheramine, stir evenly, evacuate, and obtain modified epoxy resin.

[0084] Step 6: Preparation of copper clad laminate:

[0085] Preparation of epoxy resin composition:

[0086] Take modified epoxy resin, epoxy resin, dicyandiamide, 2-methylimidazole, silicon dioxide, and organic solvent dimethylformamide, heat at 93° C., mix well, and cool to obtain an epoxy resin composition;

[0087] The epoxy resin composition comprises the following ingredients: 280 parts of modified epoxy resin, 135 parts of epoxy resin, 57 parts of dicyandiamide, 0.2 parts of 2-methylimidazole, 12 parts of silicon dioxide, and 85 parts of organic solvent dimethylformamide;

[0088] Take the epoxy resin composition to impregnate 7628 glass cloth, dry it at 125℃ to obtain a prepreg; take 3 prepregs and overlap them, cover the upper and lower surfaces with 35μm thick electrolytic copper foil, and heat it at 215℃ with 25Kg / cm 2 The copper clad laminate was obtained by hot pressing for 190 min.

[0089] Comparative Example 2: 3-glycidyloxypropyltrimethoxysilane was not used to modify the cellulose-aluminum hydroxide composite, and the rest was the same as Example 1:

[0090] Step 1: Preparation of cellulose-aluminum hydroxide complex:

[0091] Take 20g of cellulose and 120mL of anhydrous ethanol, stir evenly, add 0.2g of OP-10 emulsifier dropwise, stir for 25min, add 40g of 16.7wt% aluminum chloride aqueous solution, stir for 18min, heat to 60°C, slowly add 100mL of 8wt% sodium bicarbonate solution, stir for 2.3h, filter, wash and dry to obtain cellulose-aluminum hydroxide composite;

[0092] Step 2: Preparation of fluorinated graphene:

[0093] Take 1 g of polyvinyl pyrrolidone and 100 mL of ethanol, stir evenly, add 0.2 g of fluorinated graphene, disperse by ultrasonication, then stir for 11 h, centrifuge, take the supernatant, filter, wash, and dry to obtain fluorinated graphene;

[0094] Step 3: Preparation of urushiol-modified composite filler:

[0095] Take 6 g of urushiol and 100 mL of anhydrous ethanol, stir evenly, add 0.2 g of fluorinated graphene, disperse by ultrasonication, heat to 97 ° C, stir for 25 h, add 2 g of cellulose-aluminum hydroxide composite, continue stirring for 72 h, filter, wash, and dry to obtain urushiol-modified composite filler;

[0096] Step 5: Preparation of modified epoxy resin:

[0097] Take 7g of lacquer phenol modified composite filler and 50mL of deionized water, stir evenly, add 33g of polyethylene glycol diglycidyl ether, stir at 83°C until the deionized water is completely evaporated, add 78g of bisphenol A diglycidyl ether, stir for 2.5h, cool, add 20.5g of polyetheramine, stir evenly, evacuate, and obtain modified epoxy resin.

[0098] Step 6: Preparation of copper clad laminate:

[0099] Preparation of epoxy resin composition:

[0100] Take modified epoxy resin, epoxy resin, dicyandiamide, 2-methylimidazole, silicon dioxide, and organic solvent dimethylformamide, heat at 93° C., mix well, and cool to obtain an epoxy resin composition;

[0101] The epoxy resin composition comprises the following ingredients: 280 parts of modified epoxy resin, 135 parts of epoxy resin, 57 parts of dicyandiamide, 0.2 parts of 2-methylimidazole, 12 parts of silicon dioxide, and 85 parts of organic solvent dimethylformamide;

[0102] Take the epoxy resin composition to impregnate 7628 glass cloth, dry it at 125℃ to obtain a prepreg; take 3 prepregs and overlap them, cover the upper and lower surfaces with 35μm thick electrolytic copper foil, and heat it at 215℃ with 25Kg / cm 2 The copper clad laminate was obtained by hot pressing for 190 min.

[0103] Comparative Example 3: The mass ratio of urushiol, fluorinated graphene, and modified cellulose-aluminum hydroxide composite is controlled to be 5:0.2:1, and the rest is the same as Example 1:

[0104] Step 1: Preparation of cellulose-aluminum hydroxide complex:

[0105] Take 20g of cellulose and 120mL of anhydrous ethanol, stir evenly, add 0.2g of OP-10 emulsifier dropwise, stir for 25min, add 40g of 16.7wt% aluminum chloride aqueous solution, stir for 18min, heat to 60°C, slowly add 100mL of 8wt% sodium bicarbonate solution, stir for 2.3h, filter, wash and dry to obtain cellulose-aluminum hydroxide composite;

[0106] Step 2: Preparation of modified cellulose-aluminum hydroxide composite:

[0107] Take 80 mL of ethanol and 4 mL of deionized water, add glacial acetic acid dropwise, adjust the pH value of the solution to 4, add 2 mL of 3-glycidyloxypropyltrimethoxysilane, stir for 35 min, add 1.5 g of cellulose-aluminum hydroxide complex, heat to 67 ° C, stir for 8 h, filter, wash and dry to obtain a modified cellulose-aluminum hydroxide complex;

[0108] Step 3: Preparation of fluorinated graphene:

[0109] Take 1 g of polyvinyl pyrrolidone and 100 mL of ethanol, stir evenly, add 0.2 g of fluorinated graphene, disperse by ultrasonication, then stir for 11 h, centrifuge, take the supernatant, filter, wash, and dry to obtain fluorinated graphene;

[0110] Step 4: Preparation of urushiol-modified composite filler:

[0111] Take 5 g of urushiol and 100 mL of anhydrous ethanol, stir evenly, add 0.2 g of fluorinated graphene, disperse by ultrasonication, heat to 97 ° C, stir for 25 h, add 1 g of modified cellulose-aluminum hydroxide composite, continue stirring for 72 h, filter, wash, and dry to obtain urushiol-modified composite filler;

[0112] Step 5: Preparation of modified epoxy resin:

[0113] Take 7g of lacquer phenol modified composite filler and 50mL of deionized water, stir evenly, add 33g of polyethylene glycol diglycidyl ether, stir at 83°C until the deionized water is completely evaporated, add 78g of bisphenol A diglycidyl ether, stir for 2.5h, cool, add 20.5g of polyetheramine, stir evenly, evacuate, and obtain modified epoxy resin.

[0114] Step 6: Preparation of copper clad laminate:

[0115] Preparation of epoxy resin composition:

[0116] Take modified epoxy resin, epoxy resin, dicyandiamide, 2-methylimidazole, silicon dioxide, and organic solvent dimethylformamide, heat at 93° C., mix well, and cool to obtain an epoxy resin composition;

[0117] The epoxy resin composition comprises the following ingredients: 280 parts of modified epoxy resin, 135 parts of epoxy resin, 57 parts of dicyandiamide, 0.2 parts of 2-methylimidazole, 12 parts of silicon dioxide, and 85 parts of organic solvent dimethylformamide;

[0118] Take the epoxy resin composition to impregnate 7628 glass cloth, dry it at 125℃ to obtain a prepreg; take 3 prepregs and overlap them, cover the upper and lower surfaces with 35μm thick electrolytic copper foil, and heat it at 215℃ with 25Kg / cm 2 The copper clad laminate was obtained by hot pressing for 190 min.

[0119] experiment:

[0120] The copper clad laminates prepared in Examples 1-3 and Comparative Examples 1-3 were used for performance testing. The peel strength was tested according to 2.4.8 of IPC-TM-650. The bending strength of the copper clad laminates was tested using a universal material testing machine. The copper clad laminates were immersed in an 18% hydrochloric acid aqueous solution for 2 hours, taken out, and the peel strength was tested again. The data obtained are shown in the following table:

[0121]

[0122] Conclusion: In comparative example 1, urushiol is not added, the adhesion between fluorinated graphene and modified cellulose-aluminum hydroxide composite is deteriorated, and the dispersion of filler is deteriorated, which affects the performance of copper clad laminate. In comparative example 2, 3-glycidyloxypropyltrimethoxysilane is not used to modify cellulose-aluminum hydroxide composite, and the peel strength and bending strength of copper clad laminate are slightly reduced. In comparative example 3, the mass ratio of urushiol, fluorinated graphene, and modified cellulose-aluminum hydroxide composite is controlled to be 5:0.2:1. At this time, the addition amount of urushiol and modified cellulose-aluminum hydroxide composite is reduced, and the corrosion resistance and peel strength of copper clad laminate are deteriorated.

[0123] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a composite filler-filled high-toughness corrosion-resistant copper-clad laminate, characterized in that: The following steps are involved: Step 1: Take urushiol and anhydrous ethanol, stir evenly, add fluorinated graphene, ultrasonically disperse, heat to 95-100° C., stir for 24-26 hours, add modified cellulose-aluminum hydroxide complex, continue stirring for 70-74 hours, filter, wash, and dry to obtain urushiol-modified composite filler; Step 2: Take lacquer phenol modified composite filler and deionized water, stir evenly, add polyethylene glycol diglycidyl ether, stir at 80-85° C. until the deionized water is completely evaporated, add bisphenol A diglycidyl ether, stir for 2-3 hours, cool, add polyetheramine, stir evenly, evacuate, and obtain modified epoxy resin; Step 3: Take the modified epoxy resin, epoxy resin, dicyandiamide, 2-methylimidazole, silicon dioxide, and an organic solvent, heat at 90-95° C., mix well, and cool to obtain an epoxy resin composition; Step 4: Take the epoxy resin composition to impregnate the glass cloth, dry it, and obtain a prepreg; take 3-4 prepregs and overlap them, cover the upper and lower surfaces with electrolytic copper foil, and hot press them at 210-220° C. to obtain a copper clad laminate; The preparation method of the fluorinated graphene is as follows: polyvinyl pyrrolidone and ethanol are mixed evenly, the fluorinated graphene is added, ultrasonic dispersion is performed, and then the mixture is stirred for 10-12 hours, centrifuged, the supernatant is collected, filtered, washed, and dried to obtain the fluorinated graphene; The preparation method of the modified cellulose-aluminum hydroxide composite is as follows: take ethanol and deionized water, drop glacial acetic acid, add a silane coupling agent, stir for 30-40 minutes, add the cellulose-aluminum hydroxide composite, heat to 65-70° C., stir for 7-9 hours, filter, wash, and dry to obtain the modified cellulose-aluminum hydroxide composite; In step 1, the mass ratio of urushiol, fluorinated graphene, and modified cellulose-aluminum hydroxide composite is (6-7): (0.1-0.3): (2-3); The epoxy resin composition comprises the following components: 270-290 parts of modified epoxy resin, 130-140 parts of epoxy resin, 55-60 parts of dicyandiamide, 0.2-0.4 parts of 2-methylimidazole, 10-15 parts of silicon dioxide, and 80-90 parts of organic solvent; The preparation method of the cellulose-aluminum hydroxide complex is as follows: take cellulose and anhydrous ethanol, stir evenly, drop OP-10 emulsifier, stir for 20-30 minutes, add aluminum chloride aqueous solution, stir for 15-20 minutes, heat to 55-65° C., slowly add sodium bicarbonate solution, stir for 2-2.5 hours, filter, wash and dry to obtain the cellulose-aluminum hydroxide complex.

2. The method for preparing a composite filler-filled high-toughness corrosion-resistant copper-clad laminate according to claim 1, characterized in that: The silane coupling agent is 3-glycidyloxypropyltrimethoxysilane.

3. The method for preparing a composite filler-filled high-toughness corrosion-resistant copper-clad laminate according to claim 1, characterized in that: The mass ratio of urushiol, fluorinated graphene, and modified cellulose-aluminum hydroxide composite is 6:(0.2-0.3):(2-2.5).

4. A composite filler filled high-toughness corrosion-resistant copper clad laminate prepared according to the method for preparing a composite filler filled high-toughness corrosion-resistant copper clad laminate according to any one of claims 1 to 3.

Citation Information

Patent Citations

  • Aluminum-based copper clad laminate, and preparation method thereof

    CN105235315A

  • Fluorinated graphene nanometer medicine carrier, and preparation method and application thereof

    CN106421804A